The true intellectual system of the universe : the first part ; wherein, all the reason and philosophy of atheism is confuted ; and its impossibility demonstrated - Cudworth, Ralph (Richard Royston, 1678)
"Originally, I intended only a discourse concerning liberty and necessity, against the fatal necessity of all actions and events, which upon whatsoever ground or principles maintained, will serve the design of atheism, and undermine Christianity and all religion, as taking away all guilt and blame, punishments, and rewards, and plainly rendering a day of judgment ridiculous. But afterwards I considered that this which is indeed a controversy, concerning the true intellectual system of the universe, does, in the full extent thereof, take in other things; the necessity of all actions and events being maintained by several person, upon very different grounds, according to tripartite fatalism. First, the democritic fate is nothing but the material necessity of all things without a God"--Preface. (PsycINFO Database Record (c) 2012 APA, all rights reserved)